BENTENG KRATON PLERET: DATA HISTORIS DAN DATA ARKEOLOGI - Alifah; Hery Priswanto (Berkala Arkeologi, 2012)
As a part of a palace building, a fortress is one of the building components that must exist. A fortress is also found at Pleret Palace. The historical data obtained form Dutch records and chronicles mention that the Palace is equipped with a square-shaped fortress with a shield shape frontage. Then how the suitability of these data with archaeological evidence found at this site. This paper describes the historical data relating to the Pleret Palace fortress as well as archaeological data that have been found. Both data are compared to reveal the form, components, layout, and materials of the Pleret Palace fortress.